Trainees' Attributes and Attitudes: Neglected Influences on Training Effectiveness - Noe, Raymond A. (Academy of Management Review, 1986)
Studies of the influence of trainees' characteristics on training effectiveness have focused on the level of ability necessary to learn program content. Motivational and environmental influences of training effectiveness have received little attention. This analysis integrates important motivational and situational factors from organizational behavior theory and research into a model which describes how trainees' attributes and attitudes may influence the effectiveness of training.